An Action Research Through Cooperative Learning To Improve Studentsâ Portfolios - *, Suratni (Sebelas Maret University, 2016)
This article is based on a classroom action research (CAR). In this research, I have acted as a Lecturerin CAR. This CAR has involved students in one class of Publishing Study Program Batch 6 Semester 3in Politeknik Negeri Media Kreatif (PoliMedia) Jakarta. By applying a cooperative learning strategy, Iset out to make magazines as a result of the writing assignments on English lesson. Magazines arechosen because the students have got writing and editing skills from English lesson, and layouting skillsfrom Digital Graphics lesson. It means that the students have been taught to write and edit manuscripts,and they also have learned how to design magazines cover and content. During sixteen weeks, thestudents followed the process of creating magazines. Finally, the students can increase their writing andediting capabilities, and thus help students to make their portfolios.